PELATIHAN COACHING CLINIC SISTEMATIKA SENAM AEROBIC - Eko Rudiansyah; Cossato G Yeriko; Wendi Wendi; Lorensius Megi (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2023)
The Community Partnership Program which has been implemented in partnership with the Indonesian National Sports Committee of Melawi Regency, Sports coaching and development is part of an effort to improve the quality of Indonesian people aimed at improving the physical and spiritual health of the community. The Coaching Clinic training on the systematics of aerobic exercise which is carried out in order to overcome problems is carried out with an approach method that focuses on a participatory approach in every student of the STKIP Melawi physical education study program. At the time of implementation of activities as a whole ran smoothly. However, there were several obstacles encountered during the implementation of the activity, including: Lack of understanding of students about aerobics so that when asked about basic gymnastic movements they could not answer, student participants had difficulty distinguishing warm-up, core and cool-down movements, and students were still not ready to guide aerobics in front of other participants. The results of the implementation of the Aerobic Gymnastics Systematic Coaching Clinic made the practice results liked by all training participants even though there were still many participants who were afraid to become aerobic gymnastics instructors.